2022
DOI: 10.1111/jre.13086
|View full text |Cite
|
Sign up to set email alerts
|

Gingival tissue samples from periodontitis patients demonstrate epithelial–mesenchymal transition phenotype

Abstract: Objective: To determine the expression of key epithelial-mesenchymal transition (EMT) markers in gingival tissue samples collected from patients with periodontitis.Background: Epithelial-mesenchymal transition is a process responsible for shifting epithelial-phenotype to mesenchymal-phenotype leading to loss of epithelial-barrier function. Thus, EMT could be involved as a pathogenic mechanism in periodontitis as both conditions share common promoters and signalling pathways.Materials and Methods: Gingival tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
1
5
0
1
Order By: Relevance
“…Consistent with this observation, the level of soluble E‐cadherin in salivary samples of periodontitis patients was found to be significantly higher than in healthy controls 21,22 . Furthermore, immunohistochemical analysis of periodontally diseased tissue samples demonstrated reduced E‐cadherin levels 16 …”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…Consistent with this observation, the level of soluble E‐cadherin in salivary samples of periodontitis patients was found to be significantly higher than in healthy controls 21,22 . Furthermore, immunohistochemical analysis of periodontally diseased tissue samples demonstrated reduced E‐cadherin levels 16 …”
Section: Introductionsupporting
confidence: 72%
“…Recent immunohistochemical studies have indicated that the expression of E‐cadherin is significantly reduced in biopsies collected from periodontally‐diseased sites 16 . Previous work has also found a significant increase in the concentration of β‐catenin, a key molecule responsible for connecting E‐cadherin to the cytoskeleton, in GCF of periodontitis patients which indirectly suggesting the release of E‐cadherin 38 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations